2009
DOI: 10.1021/jo9018478
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth(III) Triflate-Catalyzed Direct Conversion of Corticosteroids into Highly Functionalized 17-Ketosteroids by Cleavage of the C17-Dihydroxyacetone Side Chain

Abstract: The use of bismuth(III) triflate as catalyst for the direct conversion of corticosteroids into highly functionalized 17-ketosteroids by cleavage of the C17-dihydroxyacetone side chain is reported. This catalytic process is very chemoselective, since functionalities of the starting corticosteroids, such as Delta(4)-3-keto, Delta(1,4)-3-keto, 11beta-hydroxyl, and 9beta,11beta-epoxide, remained intact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…A quite recent report showed that Bi(OTf) 3 ·xH 2 O is an efficient catalyst for the conversion of corticosteroids into highly functionalized 17-ketosteroids, by cleavage of the C17-dihydroxyacetone side chain [ 99 ]. This reaction was typically performed using large amounts of oxidative or basic reactants [ 100 , 101 , 102 ].…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A quite recent report showed that Bi(OTf) 3 ·xH 2 O is an efficient catalyst for the conversion of corticosteroids into highly functionalized 17-ketosteroids, by cleavage of the C17-dihydroxyacetone side chain [ 99 ]. This reaction was typically performed using large amounts of oxidative or basic reactants [ 100 , 101 , 102 ].…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…The process proved to be very chemoselective, since functionalities of the starting corticosteroids, such as Δ 4 -3-keto, Δ 1,4 -3-keto, 11β-hydroxyl, and 9β,11β-epoxide, remained intact [ 99 ]. As an important drug class in the treatment of a variety of clinical situations [ 103 ], corticosteroids are readily available compounds.…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In related studies, Bi(OTf ) 3 was also used as a catalyst for the direct conversion of corticosteroids into highly functionalized 17-ketosteroids by cleavage of the C17dihydroxyacetone side chain. 78 Participation of an in situ generated Brønsted acid species from Bi(OTf ) 3 was also pointed out for the opening of oleanolic hydroxy-γ-lactones into the corresponding 12-oxo-28-carboxylic acid derivatives. 79…”
Section: Wagner-meerwein Rearrangementmentioning
confidence: 96%
“…Bismuth is nontoxic and relatively cheap, and bismuth compounds have been widely used in catalysis and organic synthesis [1]. Inorganic bismuth compounds such as bismuth halides have been used as Lewis acid catalysts in a number of organic reactions [1][2][3][4][5]. However, the utilization of organobismuth compounds trivalent and pentavalent for organic synthesis is rarely reported partly due to the unstable nature of the Bi-C bonds [6,7].…”
Section: Introductionmentioning
confidence: 99%